THE POTENTIAL OF THE AGRICULTURAL AND NON-AGRICULTURAL SECTORS FOR ECONOMIC GROWTH REGION IN BEKASI CITY - Beatrice, Beatrice; Setiawan, Johan; Anggraeni, Dian; Sariyoga, Setiawan (AGRIBUSINESS JOURNAL, 2024)
This study aims to analyze the sectoral dynamics in the Bekasi City economy, focusing on the relative contribution of the agricultural and non-agricultural sectors to regional economic growth. Through a quantitative approach, using Location Quotient and Shift-Share analysis, this study identifies the shift in economic structure from the primary sector towards the secondary and tertiary sectors. The results show that the non-agricultural sector, especially trade and services, is increasingly dominant in driving the economic growth of Bekasi City. This finding indicates the importance of economic diversification and increasing the competitiveness of leading sectors in supporting sustainable development in Bekasi City. This research provides implications for the formulation of more effective regional economic development policies.